Influence of biobased polyol type on the properties of polyurethane hotmelt adhesives for footwear joints - M. P. Carbonell-Blasco (SpringerOpen, 2021)
Abstract Polyurethanes, one of the most used polymers worldwide, are strongly dependent of non-renewable fossil resources. Thus, boosting the production of new polyurethanes based on more sustainable raw materials is crucial to move towards the footwear industry decarbonisation. The aim of this study is to synthesise and characterise reactive hotmelt polyurethanes from biomass and CO2-based polyols as bioadhesives for the footwear industry. The influence of biobased polyols on the polyurethane structure, and therefore, on their final properties was analysed by different experimental techniques such us Fourier transform infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), Melting viscosity, Softening temperature and T-peel strength test, in order to assess their viability for the upper to sole bonding process. The results obtained indicated that the incorporation of different amounts of the biobased polyols produces changes in the structure and final performance of the polyurethanes. Therefore, adhesion test carried out by the T-peel test 72 h after the upper -to- sole bonding of the sustainable adhesives show high final adhesion values. These sustainable raw materials provide polyurethane adhesives with additional beneficial non-toxicity and sustainable characteristics, without harming their properties during their useful life.